Methods of soil analysis (Wisconsin, 1982)
This book reported soil surface is substantially polluted by atmospheric deposition, the surface few centimeters and especially surface organic materials may be very high in Pb compared with materials at greater depths,...
Keywords: Soil microbiology,Soils,Sinh học đất; Methodology,Analysis,Phương pháp học